2004
DOI: 10.1017/s0022377804002909
|View full text |Cite
|
Sign up to set email alerts
|

The transformation of MHD Alfvén waves in space plasma

Abstract: The nonlinear mechanism of the transformation of magnetohydrodynamic (MHD) Alfvén waves to kinetic Alfvén waves (KAWs) in the homogeneous magnetized plasma with small plasma parameter β Ӷ 1 is investigated. As the generation mechanism, the parametric instability where the MHD Alfvén wave is the pumping wave is considered. On the basis of the two-fluid MHD and Vlasov equation, the nonlinear dispersion relation describing three-waves interaction, the instability growth rate and the threshold of the instability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…This requires much more detailed numerical and analytical analysis. For more efficient heating due to MHD waves, these waves must transfer their energy to smaller length scales due to various types of instability and dissipation mechanisms (see Fedun et al, 2004;Copil et al, 2010). In order to resolve the dissipation numerically very powerful high performance computational equipment is needed and we hope to make the first steps in this direction in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…This requires much more detailed numerical and analytical analysis. For more efficient heating due to MHD waves, these waves must transfer their energy to smaller length scales due to various types of instability and dissipation mechanisms (see Fedun et al, 2004;Copil et al, 2010). In order to resolve the dissipation numerically very powerful high performance computational equipment is needed and we hope to make the first steps in this direction in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that the higher‐frequency waves are kinetic Alfvén waves, that they are damped when they are near or above the local ion gyrofrequency, and that they are also generated between Polar and FAST. This generation mechanism is open to speculation, but the energy to generate them may come from the lower‐frequency Alfvén waves [ Chaston et al , 2003b; Wu , 2003; Fedun et al , 2004; Watt et al , 2004; Voitenko and Goossens , 2005]. Since kinetic Alfvén waves contain a parallel electric field which can accelerate electrons [ Hasegawa , 1976; Goertz and Boswell , 1979] conversion of the lower‐frequency Alfvén waves into kinetic Alfvén waves provides a possible mechanism for the lower‐frequency Alfvén wave Poynting flux at Polar to power the auroral acceleration process.…”
Section: Observations and Discussionmentioning
confidence: 99%
“…These motions are found at photospheric bright points, thus suggesting the magnetic nature of the photospheric vortices. On the other hand, as it has recently been demonstrated by forward modelling (Shelyag et al, 2008;Fedun et al, 2009Fedun et al, , 2011, the motions, which occur at the footpoints of photospheric magnetic flux tubes, effectively leak into the higher layers of the solar atmosphere thus eventually reaching the corona and transporting energy into it (Fedun et al, 2004;Erdélyi and Fedun, 2007;Taroyan, 2008; Correspondence to: S. Shelyag (s.shelyag@qub.ac.uk) Taroyan and Erdélyi, 2009;Antolin and Shibata, 2010). Thus, it is suggested that vortex motions in the photosphere may act as one of the potential mechanisms of energy supply to the upper solar atmosphere.…”
Section: Introductionmentioning
confidence: 99%